2016
DOI: 10.3390/vetsci3020008
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Animals in a One Health Approach to Harmful Cyanobacterial and Algal Blooms

Abstract: People, domestic animals, and wildlife are all exposed to numerous environmental threats, including harmful algal blooms (HABs). However, because animals exhibit wide variations in diet, land use and biology, they are often more frequently or heavily exposed to HAB toxins than are people occupying the same habitat, making them sentinels for human exposures. Historically, we have taken advantage of unique physiological characteristics of animals, such as the sensitivity of canaries to carbon monoxide, to more q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…have occurred in the SFE during the summer since 1999 [ 5 6 ]. Microcystis and other harmful cyanobacteria can degrade water quality by producing cyanotoxins or other toxic compounds [ 7 – 9 ]. Laboratory experiments have demonstrated that Microcystis directly or indirectly affect the health (e.g., growth) and survival of embryo to sub-adult fishes [ 10 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…have occurred in the SFE during the summer since 1999 [ 5 6 ]. Microcystis and other harmful cyanobacteria can degrade water quality by producing cyanotoxins or other toxic compounds [ 7 – 9 ]. Laboratory experiments have demonstrated that Microcystis directly or indirectly affect the health (e.g., growth) and survival of embryo to sub-adult fishes [ 10 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Humans may also encounter these chemicals by consuming contaminated finfish and shellfish, and via agricultural products irrigated with toxin-laden water [13,14,15,16]. Various cyanotoxins are also consequential to domestic animals, livestock, and wildlife, sometimes resulting in significant mortality events [15,17]. The best-studied and arguably most prevalent of these compounds are the cyclic heptapeptide microcystins, followed by nodularins [18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…MCs may also bio-accumulate in food chain and hence humans could be exposed to trace levels via the ingestion of contaminated food as well (Larson et al, 2014;Greer et al, 2018). Mortality cases of animals such as dogs, cows, and birds were linked to the consumption of water contaminated with such toxins (Hilborn and Beasley, 2015.;Backer and Miller, 2016). Symptoms of human exposure to MCs include skin rashes, ear and eye irritation, asthma, allergic reactions, sporadic dry cough, vomiting, diarrhea, abdominal pain, pneumonia.…”
Section: Introductionmentioning
confidence: 99%